2017
DOI: 10.7150/ijms.19480
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and Ileocolonoscopic Characteristics in Patients with Nodular Lymphoid Hyperplasia in the Terminal Ileum

Abstract: Nodular lymphoid hyperplasia (NLH) in the small intestine is a rare benign lesion, characterized by the presence of multiple small nodules on the surface of the intestine. To define the clinicopathological and colonoscopic characteristics in Chinese patients with ileal NLH, we collected 65 patients with NLH in the terminal ileum from the endoscopic database in our hospital and clinical data from medical records. Histology and immunohistochemical staining were performed in the biopsies. The results demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
(34 reference statements)
0
3
0
1
Order By: Relevance
“…Second, the male-female ratio in the NLH group was not balanced in this study due to the nature of terminal ileal NLH, which is thought to be significantly more common in men than women. Although the incidence of terminal ileal NLH in both men and women has not been investigated through a large-scale study, Lin et al observed that males outnumbered females by approximately four to one in a small-scale study[ 3 ]; their results support, to a certain degree, the suggestion that there is a higher frequence of terminal ileal NLH in males than females. We also performed a correlation analysis to compare the intestinal flora with gender using the Multivariable Association with Linear Models2, and we found that there was no correlation between the intestinal floras and gender at the phylum, genus, or OTU levels.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Second, the male-female ratio in the NLH group was not balanced in this study due to the nature of terminal ileal NLH, which is thought to be significantly more common in men than women. Although the incidence of terminal ileal NLH in both men and women has not been investigated through a large-scale study, Lin et al observed that males outnumbered females by approximately four to one in a small-scale study[ 3 ]; their results support, to a certain degree, the suggestion that there is a higher frequence of terminal ileal NLH in males than females. We also performed a correlation analysis to compare the intestinal flora with gender using the Multivariable Association with Linear Models2, and we found that there was no correlation between the intestinal floras and gender at the phylum, genus, or OTU levels.…”
Section: Discussionmentioning
confidence: 96%
“…The diagnosis of NLH is mainly based on endoscopic and histological examinations, markedly including the presence of hyperplastic lymphoid follicles and mitotically active germinal centers with well-defined lymphocytic mantles[ 2 ]. Terminal ileal NLH is a type of NLH, and patients with terminal ileal NLH demonstrate multiple symptoms that seriously reduce the individual’s quality of life, such as chronic diarrhea, abdominal pain, hematochezia, anemia, hypoproteinemia, among other symptoms[ 3 ]. Patients with irritable bowel syndrome are more likely to accompany with NLH[ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…This condition does not necessitate any intervention, and treatment is mainly relevant to the associated conditions (38).…”
Section: Nodular Lymphoid Hyperplasia (Nlh)mentioning
confidence: 99%
“…Известно, что лимфоидная ткань слизистой оболочки толстой кишки включает в себя интраэпителиальные лимфоциты покровного и криптального эпителия, лимфоциты собственной пластинки СО и лимфоидных узелков и состоит из основных популяций Т-лимфоцитов, экспрессирующих CD4 и CD8 маркёры. Лимфоциты поверхностного эпителия в подавляющем большинстве являются CD8+ Т-лимфоцитами (80-90%-антигенный маркёр супрессорных и цитотоксических Т-киллеров с угнетением иммунного ответа, торможением выработки антител В -лимфоцитами), в то время как основная масса CD4+ Т-лимфоцитов находится в собственной пластинке СО и является представителем эффекторных лимфоцитов при воспалительном процессе (маркёр Т-хелперов с распознаванием молекул процессированного антигена [5]. При этом большое значение в оценке состояния иммунной системы имеет не столько абсолютное значение содержания популяции CD4+ и CD8+ Т-лимфоцитов, а их соотношение CD4/ CD8, что выражается иммунорегуляторным индексом -ИРИ, характеризующим интенсивность иммунного ответа.…”
Section: Introductionunclassified